Detection of Neoplastic Gastric Lesions Using Capsule Endoscopy: Pilot Study - Byoung Yeon Jun; Chul-Hyun Lim; Wook Hyun Lee; Jin Su Kim; Jae Myung Park; In Seok Lee; Sang Woo Kim; Myung-Gyu Choi (Gastroenterology Research and Practice)
Objectives. Capsule endoscopy is relatively noninvasive method and its use extends from the small bowel to the esophagus and colon. The aim of this study was to evaluate the feasibility and acceptability of capsule endoscopy for neoplastic gastric lesions. Methods. Capsule endoscopy (Pillcam ESO) was performed within 48 hours of esophagogastroduodenoscopy for eight patients who were diagnosed with gastric cancers, the size of which were less than 4 cm and who presented written consent. Patients changed position in a specified designed sequence every 30 seconds after capsule ingestion. Position change was repeated with ingestion of an effervescent agent. The rate of detection of intragastric lesions, observation of normal gastric anatomy and patient satisfaction between capsule endoscopy and esophagogastroduodenoscopy were compared. Results. Capsule endoscopy found four out of eight gastric lesions. The gastroesophageal junction was observed in seven of the eight cases, pyloric ring in five of the eight cases, and gastric angle in four of the eight cases. The patient satisfaction assessment questionnaire rated capsule endoscopy significantly higher than upper endoscopy in all categories. Conclusions. Capsule endoscopy was less effective than esophagogastroduodenoscopy and showed limited value in this feasibility study.